PERANAN PENYULUH PERTANIAN DALAM PENINGKATAN KINERJA USAHA PERKEBUNAN KARET DI KECAMATAN NEGERI BESAR KABUPATEN WAY KANAN: THE ROLE OF AGRICULTURAL EXTENSIONERS IN INCREASING RUBBER PLANTATION BUSINESS PERFORMANCE IN THE DISTRICT OF NEGERI BESAR, WAY KANAN - Danapriatna, Nana; Ismarani, Ismarani; Puspito, Puji (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
Rubber plantations in Indonesia is largely managed by the Government and most private rubber plantations owned by the people even though on a small scale but the number of people large enough rubber estates. The farmers ' efforts to improve the results of its production is still very far from expected, this of course requires cooperation between farmers and agricultural extension officers as stakeholders in regards to the transfer of various information. This research aims to know the role of agricultural extension officers in farmer group, to know the performance of the farming, and analyze the role of agricultural extension officers with performance rubber plantation farming in the country big, Way Kanan Regency. The results showed the role of farmer dikelompok extension officers have not been fullest but already entered in the category quite nicely. Application of technology of rubber cultivation had already entered in that category either because farmers in its application in accordance with the recommended by the Plantation Counties the Way Kanan. The role of agricultural extension officers relations with performance rubber plantation farming is very low and not significant impact on rubber farmers in the land of big, Way Kanan Regency.